Analisis Balok Beton Bertulang Tampang T Yang Diperkuat Dengan Wire Rope Menggunakan Program Response-2000 Dan Metode Pias - Anggun Tri Atmajayanti (Dinamika Rekayasa, 2013)
This study aims at finding out the comparison of the results of analysis using Response-2000 and discrete element method and of experiment on T-section reinforced concrete beam strengthened using wire rope. The modeling was made on two T-section beams, where one beam was without strengthening and another beam was with strengthening using two wire ropes of 10mm. Results indicate that the ratios of increase in flexural capacity as results of the analysis using Response-2000 and discrete element method compared to results of the experiment for the control beam were 1.01 and 1.04, respectively, while the ratios of decrease for the strengthened beam were 0.84 and 0.87, respectively. A ductility index for the control beam as result of the analysis using Response- 2000 and discrete element method decreased compared with results of the experiment with ratios of 0.31 and 0.60, respectively. A ductility index for the strengthened beam as result of the analysis using Response-2000 and discrete element method increased compared with results of the experiment with ratios of 1.19 and 1.92, respectively. The ratios of increase in the initial stiffness as result of the analysis using Response-2000 and discrete element method compared with result of the experiment for the control beam were 2.85 and 3.33, respectively, and the ratios of increase in equivalent stiffness as result of the analysis using Response-2000 and discrete element method were 1.62 and 1.42, respectively. The ratios of increase in initial stiffness for the strengthened beam as result of the analysis using Response-2000 and discrete element method compared with result of the experiment were 3.70 and 5.26, respectively, while those for equivalent stiffness were 3.16 and 2.75, respectively.